Recent advances in heavy metal/metalloid ion treatment from wastewater using nanocomposites and bionanocomposites - Singh, Namita; Yadav, Annu; Das, Sumistha; Debnath, Nitai (Frontiers in Nanotechnology, 2024)
Wastewater remediation is of paramount importance for the water-stressed modern civilization from the perspective of sustainable development and the management of limited freshwater resources. Contaminants such as heavy metal and metalloid ions, toxic dyes, and pathogenic microbes present in the aquatic ecosystem have adverse effects not only on the environment but also on human health. Traditional wastewater remediation processes are costly, energy-consuming, and have less efficiency in removing pollutants from wastewater. Multi-phasic nanomaterials or nanocomposites have enormous potential for removing contaminants from water bodies. These materials have an enormous tunable surface area for interacting with the target toxicants and are extremely stable in the aquatic system, but they readily agglomerate. Many research groups have exploited biosorption, bioleaching, and bioprecipitation capacities of fungal hyphae for wastewater remediation. Recently, researchers have attempted to explore the synergistic effect of the bionanocomposite of fungal hyphae and nanomaterials for removing pollutants from wastewater. This bionanocomposite has already shown promise as a superior material for wastewater treatment and can easily be separated from the polluted water for reuse over several cycles. The bionanocomposite-mediated decontamination of water can lead to a total paradigm shift in wastewater management strategies.